Analysis of the Readiness of Substructure Work Execution Methods (Bore Pile and Pile Cap Foundations) in High-Rise Building Projects - Rio Arsil; Akhirul Desman (Structures, Infrastructure, Planning, Implementation, and Legislation, 2025)
The foundation system is a critical determinant of stability in high-rise buildings, ensuring safe transfer of structural loads to the ground. This study applied a qualitative–quantitative analytical approach to assess the readiness of substructure execution methods, focusing on bored pile and pile cap foundations. Readiness was evaluated using four variables technical, geotechnical, economic, and safety based on data from technical reports, Indonesian National Standards, and recent international literature. Numerical calculations of bearing capacity and settlement were processed with Microsoft Excel, while SPSS was used in a limited scope for descriptive statistics to validate soil parameters. A case study of pad footing design (1.8 × 1.8 m, depth 1.5 m) served as a baseline. Results indicated that the allowable bearing capacity (127.14 kN/m²) exceeded applied loads, confirming adequacy for a two-story building. However, shallow foundations are unsuitable for high-rise structures due to larger axial and lateral forces and more complex soil conditions. The study concludes that bored piles with pile caps are essential for high-rise construction, offering deeper load transfer, controlled settlement, and effective load distribution. Readiness depends on accurate geotechnical investigation, compliance with standards, technology availability, cost feasibility, and safety assurance. Future work should integrate numerical modeling, in-situ monitoring, and digital tools such as BIM and IoT to enhance prediction accuracy and minimize risks.